A compact X-shaped mechanism based 3-DOF anti-vibration unit with enhanced tunable QZS property. (1st April 2022) - Chai, Yuyang; Jing, Xingjian; Guo, Yingqing
Graphical abstract: Highlights: A novel passive and compact 3-DOF anti-vibration unit with an enlarged QZS range. The unit is composed by passive X-shaped linkage mechanisms with novel spring connection. Offering excellent vibration isolation in X, Z, and RY directions with adjustable properties. Very flexible for constructing multi-DOF (1 to 6 DOFs) vibration isolation platform with this unit. New insight into engineering multi-DOF anti-vibration with the X-shaped mechanism or its variants. Abstract: Quasi-zero stiffness (QZS) systems for passive vibration isolation have been extensively studied for high static and low dynamic stiffness in practical applications. However, most existing QZS isolators are focused more on suppressing vibration transmission of a single direction, which thus presents a limitation in applications. This study presents a novel X-shaped mechanism based 3 degrees of freedom (3-DOF) anti-vibration unit with enhanced QZS effect in a large stroke, which is expected to achieve low-frequency vibration isolation in three directions simultaneously. The proposed anti-vibration unit exhibits beneficial nonlinear stiffness and damping characteristics, and it can passively achieve excellent and tunable vibration isolation performance in all three directions. The loading capacity, static stiffness and QZS zone in three directions are conducted for understanding such a 3-DOF anti-vibration unit. The influences of several design parameters including the lengths of rods, static equilibrium positions, spring stiffness, damping coefficients and excitation amplitudes on vibration isolation performance are all studied. Compared with typical spring-mass-damper (SMD) isolators, or existing traditional QZS isolators, the proposed anti-vibration structure exhibits much larger QZS area in the main vibration isolation direction, can be flexibly used to construct more DOF vibration isolation in a compact design, and can thus achieve excellent vibration isolation performance in more directions simultaneously with guaranteed stable equilibrium. The results of this study present a new insight into multi-direction passive vibration isolation required in many engineering practices, based on the X-shaped linkage mechanism.